The short training course organized at the USARB Scientific Library (Confluenţe Bibliologice, 2018)
The Continuing Training Department of the State University of Mol- dova, in collaboration with the Scientific Library of the „Alecu Russo” Bălţi State University, organized two short-term courses The Basics of Library and Information Sciences and Current Trends in the Moldovan Libraries (75 hours ). There were 59 librarians from the libraries of all types, especially the territorial public in the North Zone - 15 districts and the Balti municipality. The trainers were the university librarians of Balti.
Keywords: Departmental Librarianship Center; continuous professional training